Flexible electrospun fluorescent anisotropic conductive Janus-typed nanoribbon membrane. (15th June 2022) - Hu, Yaolin; Qi, Haina; Yang, Liu; Sheng, Yuqi; Xie, Yunrui; Ma, Qianli; Shao, Hong; Yu, Wensheng; Li, Dan; Dong, Xiangting
Graphical abstract: Highlights: Fluorescent anisotropic conductive Janus-typed nanoribbon array membrane is designed. Carbon black is used as conductive filler to build anisotropic conductive membrane. Conductive anisotropy of the membrane is tunable by modulating carbon black content. Membrane demonstrates enhancive red fluorescence and tunable anisotropic conduction. Percolation zone of carbon black in Janus-typed nanoribbon array membrane is gained. Abstract: Flexible multiple-functional conductive anisotropic membrane made of one-dimensional directional nanomaterial has the potential applicative prospects in advanced electronic skin and strain sensor. Nevertheless, it is hard to prepare aligned polymeric composites with poly-functional high conductive anisotropy and excellent interface properties, so it has been a vital topic to fabricate and investigate such kind of composites. In this work, the fluorescent anisotropic-conduction Janus-typed nanoribbon array membrane (named as FAJNAM for short) with [Eu(TTA)3 bipy/polymethylmethacrylate (PMMA)]//[carbon black (CB)/PMMA] Janus-typed nanoribbon as construction unit is prepared by di-axial parallel electrospinning with a di-axial parallel spinneret. Since CB will seriously affect the fluorescence intensity of the Eu(TTA)3 bipy complex, through using Janus-typed nanoribbon as construction unit, Eu complex and CB can be confined in their own regions, realizing efficacious separation of fluorescent and electrical substances to significantly reduce the adverse effects between the two functions so as to obtain excellent red fluorescence and electrical conduction. The percolation zone of CB in Janus-typed nanoribbons membrane is determined. By adjusting the content of CB, the transition from insulation to conductivity of the FAJNAM can be realized. The highest anisotropic conduction ratio reaches ca. 10 8 when the CB content is 10 %. For the first time, the crucial of critical diffusion concentration of two-phase spinning solutions in the parallel electrospinning process is advanced and studied in depth. Furthermore, the relationship between the critical diffusion concentration and the conductive aeolotropism degree has been explored. The concept of critical diffusion concentration is also applicable to other di-axial parallel electrospinning to prepare multi-functional materials, which will be of great significance to optimize electrospinning conditions. This research provides new technical support for the preparation of highly flexible, conductive anisotropy composite materials.